155k views
5 votes
In the given figure AD is median. prove that ar(triangle ABD) = ar(triangle ACD)

1 Answer

5 votes

Answer:

Proved!

Explanation:

We know that,


\bigstar\; \boxed{\sf {Area\; of\; triangle= (1)/(2) * Base * Height\;(1)/(2) * Base * Height}}

So,


\it Area\; of\; triangle, ABD= (1)/(2) * BD * AN12* BD * AN

And,


\it Area\; of\;triangle\;ADC= (1)/(2) * DC * AN =12 * BD * AN\;(1)/(2) * DC * AN = 12 * BD *AN

(As we know BD = DC )

So,

Area of triangle ABD = Area of triangle ADC

(Hence proved)


\rule{300}{1.5}

Note :

Kindly Post/Attach figure If question is related to figure.

I have Attach the figure now!

Thanks!

In the given figure AD is median. prove that ar(triangle ABD) = ar(triangle ACD)-example-1
User Platinum
by
4.7k points